Exploring the Global Emergence of Linear Programming, its Application, Benefit and Prominence: A Squint on Literature Review - Mwambazi, Chrispine Mulenga; Mbewe, Simeon; Simui, Francis (European Journal of Science, Innovation and Technology, 2024)
This work aims to review the research on the global emergence of linear programming, its application, benefit and importance. Scholarly debate has been documented over the concept, content, and purpose of linear programming, as well as its global emergence. Additionally, the article has demonstrated the importance of linear programming in enhancing economic development. Linear programming has also been found to improve corporate management, decision-making, planning, and management. Thus, the set will aid in the industrialization process, the efficient planning and administration of the world’s finite resources, particularly in developing nations. Therefore, in order to improve topic delivery, it is advised that the government, through the Ministry of Education (MoE), efficiently train and hire competent math instructors to teach linear programming in secondary schools across the nation. Moreover, it is suggested that the MoGE include linear programming in all educational levels. Finally, it is advised that math teachers prioritize delivery and incorporate a range of approaches, ideas, and techniques into their lessons.